A rare case of successful pregnancy outcome with giant paraovarian cyst: a case report and review of literature - Katke, Rajshree D.; Pagare, Priyanka; Raina, Jyoti; Singh, Kunalkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
A successful outcome of a pregnancy with huge paraovarian cyst in a 29 year old female who presented with 16 weeks of gestation with ultra-sonography suggestive of huge mesenteric cyst. Pregnancy was carried till 35 weeks of gestation. Exploratory laparotomy was done where a giant paraovariancyst of size 35cm x 20 cm x 15 cm, weighing 2kg was found. Baby was delivered by lower segment caesarean section and cystectomy was performed.